The reentry of Asian kinesiology professionals after obtaining a doctorate at higher education institutions in the U.S. - Park, Seungyeon (Frontiers in Education, 2023)
With the large increase in international doctorates at U.S. higher education institutions, little attention is being paid to former doctoral students’ cross-cultural experiences during their reentry to their home countries. Based on the re-acculturation theory as a conceptual framework, this qualitative inquiry aims to explore how study participants perceive their reentry. The findings were explained using six subthemes: (a) the renewal process, (b) ambivalence of reentry, (c) homing instinct, (d) environmental context, (e) midpoint of repatriation, and (f) different research atmospheres. The findings reveal the importance of doctorates’ flexibility to cope with each country’s academic atmosphere and respect academic cultural differences. Findings discuss the challenges that international kinesiology professionals face during the reentry, and how they resolve these difficulties for readjustment to their home country’s academic atmosphere.